The Role of Net Profit Margin (NPM), Total Asset Turnover (TATO), and Debt-to-Equity Ratio (DER) in Improving Return on Equity (ROE) of State-Owned Banks Listed on the Indonesia Stock Exchange during the 2019–2024 Period. - Najwa Nur Syahla; Rahmi Yuliana (SS&H: Studies in Social Sciences and Humanities, 2026)
This study aims to examine the influence of Net Profit Margin (NPM), Total Asset Turnover (TATO), and Debt to Equity Ratio (DER) on Return on Equity (ROE) in state-owned commercial banks listed on the Indonesia Stock Exchange during the 2019–2024 period. The research is grounded in the DuPont Analysis framework, which explains that shareholder returns are shaped by the firm's profitability, efficiency in utilizing assets, and financing structure. A quantitative research design was employed using secondary data obtained from the annual financial statements of five state-owned banks. The relationships among variables were analyzed through multiple linear regression. The empirical findings indicate that Net Profit Margin, Total Asset Turnover, and Debt to Equity Ratio each have a positive and statistically significant effect on Return on Equity, both individually and simultaneously. These findings suggest that higher profitability, more efficient asset utilization, and prudent leverage management contribute to improving shareholder returns. Accordingly, strengthening operational efficiency, optimizing asset productivity, and maintaining an appropriate capital structure are essential strategies for enhancing the financial performance of state-owned banks.